Small-sided games: alternative exercise to improve cognitive performance of youth futsal players - Moch Fath Khurrohman; Yudanto; Agus Susworo Dwi Marhaendro; Rifqi Festiawan; Rohman Hidayat (Universitas Nusantara PGRI Kediri, 2021)
Abstract Small Sided Games are an alternative exercise for athletes to improve cognitive performance which functions as a matter of quick decision making during a match. This study aims to determine in reality the application of SSG exercises to the cognitive performance of adolescent futsal athletes. This research is a type of experimental research using a one class pretest-postest design. The number of samples of the study were 20 youth futsal athletes in Banyumas Regency. The research instrument used in this study was the WAIS IV digit span test. The analysis used was the normality test, homogeneity, and paired sample t-test with a significance level of 0.05. The results of the research conducted showed that: there was a significant effect of small sided games training prizes on the cognitive performance of futsal athletes. It was shown that there would be a t-test of 0.017.